Time trends, frequency, characteristics and prognosis of short‐duration transient global amnesia. (26th February 2020) - Romoli, M.; Tuna, M. A.; Li, L.; Paciaroni, M.; Giannandrea, D.; Tordo Caprioli, F.; Lotti, A.; Eusebi, P.; Mosconi, M. G.; Pellizzaro Venti, M.; Salvadori, N.; Gili, A.; et al.
Abstract : Background and purpose: Transient global amnesia (TGA) is characterized by a sudden onset of anterograde amnesia lasting up to 24 h. One major differential for TGA is transient epileptic amnesia, which typically lasts < 1 h. However, TGA can also be short in duration and little is known about the time trends, characteristics and prognosis of TGA cases lasting < 1 h. Methods: We compared the clinical features of TGA ascertained in two independent cohort studies in Oxfordshire, UK [Oxford cohort 1977–1987 versus Oxford Vascular Study (OXVASC) 2002–2018] to determine the time trends of clinical features of TGA. Results were validated in another independent contemporary TGA cohort in Italy [Northern Umbria TGA registry (NU) 2002–2018]. We compared the risk factors, clinical features and long‐term prognosis (major cardiovascular events, recurrent TGA and seizure/epilepsy) of patients presenting with episodes lasting < 1 h versus those lasting ≥ 1 h. Results: Overall, 639 patients with TGA were included (114 Oxford cohort, 100 OXVASC, 425 NU). Compared with the original Oxford cohort, there were more cases with TGA lasting < 1 h in OXVASC [32 (32.0%) vs. 9 (8.8%)] and NU (11.8% vs. 8.8% in Oxford cohort). In both OXVASC and NU, patient age, vascular risk factors and clinical features were largely similar between those with TGA lasting < 1 h versus those lasting ≥ 1 h. Moreover, there was no difference in the long‐term risk of seizure/epilepsy or major cardiovascular events between TGA lasting < 1 h versus TGA lasting ≥ 1 h. Conclusions: Short‐duration TGA episodes (<1 h) were not uncommon and were more frequent than in earlier studies. The clinical features and long‐term prognosis of short‐duration TGA did not differ from more typical episodes lasting ≥ 1 h.